Customer preference analysis in using cash recycle machine service at Bank Syariah Indonesia - nanda safarida; Fahriansah; Novi Zikrillah (IAIN Langsa, 2022)
This study aims to analyze the level of preference of Bank Syariah Indonesia customers in using cash deposit services through the Cash Recycle Machine (CRM). This is a qualitative research with qualitative data in the form of ordinal data collected through questionnaires and compiled using a semantic differential scale with 10 predetermined attributes. The sample in this study was 100 customers of Bank Syariah Indonesia Langsa City Branch which was determined through accidental sampling technique. The research method used is the Kendall's concordance method processed with SPSS. The results of the research through the Kendall's test obtained the Kendall's value of 0.33 and the X2 value of 29.531. While the value of X2table0.05;9 is 16.918. This means that there is a relevancy of the respondent's answer preferences related to the 10 attributes used in the questionnaire. Meanwhile, 9 of 10 attributes, namely decision, distance, time period, time for deposit cash, technology, level of practicality, smooth access, durability of deposit proof, and level of risk, have a preference that tends to be positive and be taken into consideration for customers to deposit their cash through the CRM service. Except for the attribute which is related to the level of security where the average respondent agrees that it is not really be taken into customer consideration in making cash deposits through CRM service.